Identification of Catalytic Sites for Oxygen Reduction in Metal/Nitrogen-Doped Carbons with Encapsulated Metal Nanoparticles - Chen, Ming-Xi; Zhu, Mengzhao; Zuo, Ming; Chu, Sheng-Qi; Zhang, Jing; Wu, Yuen; Liang, Hai-Wei; Feng, Xinliang (Angewandte Chemie International Edition, 2020)
The development of metal-N-C materials as efficient non-precious metal (NPM) catalysts for catalysing the oxygen reduction reaction (ORR) as alternatives to platinum is important for the practical use of proton exchange membrane fuel cells (PEMFCs). However, metal-N-C materials have high structural heterogeneity. As a result of their high-temperature synthesis they often consist of metal-Nx sites and graphene-encapsulated metal nanoparticles. Thus it is hard to identify the active structure of metal-N-C catalysts. Herein, we report a low-temperature NH4Cl-treatment to etch out graphene-encapsulated nanoparticles from metal-N-C catalysts without destruction of co-existing atomically dispersed metal-Nx sites. Catalytic activity is much enhanced by this selective removal of metallic nanoparticles. Accordingly, we can confirm the spectator role of graphene-encapsulated nanoparticles and the pivotal role of metal-Nx sites in the metal-N-C materials for ORR in the acidic medium.
CRIS-Team Scopus Importer:2023-03-20
Keywords: active sites; encapsulated nanoparticles; Fe-N-C; fuel cells; oxygen reduction reaction (ORR)